Australian workplace health and safety regulatory approaches to prosecution: Hegemonising compliance. (November 2014) - Schofield, Toni; Reeve, Belinda; McCallum, Ron
Enforcement of workplace health and safety regulations remains a contentious matter, especially in the context of Australia's project to harmonise commonwealth, state and territory workplace health and safety legislation. This article presents the findings of a qualitative study investigating policies and practices associated with prosecution and enforcement in two Australian regulatory agencies, prior to harmonisation. The article finds that by 2008, both regulators had taken significant steps to render their enforcement policy and practice, particularly in relation to prosecution, more transparent and accountable to employers and the wider community. They produced detailed and publicly available enforcement policies and prosecution guidelines, reconfigured the work of the general inspectorate (confining it to routine workplace health and safety surveillance and the provision of education and advice to employers) and established a separate administrative unit responsible for investigation and prosecution. Both regulators structured prosecution processes to achieve explicitly technocratic outcomes, namely, enhanced efficiency, objectivity, timeliness, consistency and quality improvement in investigations. These processes went hand in hand with a dramatic decline in the use of prosecution in New South Wales from 2002 to 2010, and an uneven but marginal increase in Victoria for the same period. The article concludes by discussing what these findings might imply for workplace health and safety regulators' approaches to prosecution and for deterrence under Australia's new harmonised regime.